Racket sports coaches: a review of scientific production - Cardoso, Camila (2023)
BACKGROUND: Scientific productions focusing on coaches in Brazil have shown a growing sporting trend, especially since 2008, mainly in team sports. However, a scientific review on coaches of the main racket sports was not presented.OBJECTIVE: To analyze the scientific production on racket sports coaching from the journals attached to the CAPES Periodicals Portal. METHODS: Using the state of the art, the searches were carried out in the journals attached to area 21 of the CAPES Periodicals Portal. After a journal selection process, totaling 26 journals classified from A1 to B3, we used the following terms: “badminton”, “tennis”, “table tennis”, “squash”, “net sports”, “racquet sports”, “racket sports”. The terms were used in Portuguese, English and Spanish and articles published until December 2018 classified as original or review were selected. Of the 1061 articles that met the search inclusion criteria, 207 were selected as dealing with racket sports, with only 7 having the racket sports coach as the main topic.RESULTS: Tennis and table tennis were the most studied racket sports with a focus on the coach. The topics studied were: behavior, thinking, assessment and characteristics of the coach. Most studies were published in high-ranking journals (Qualis A1 and A2) in languages such as English and Spanish, while only one study was published in a Brazilian journal in Portuguese.CONCLUSION: The small scientific production on racquet sports coaches, mainly at the national level, presents itself as a potential area for the development of future studies with a focus on sports that did not present any scientific production (badminton and squash) as well as on others study topics, for example the development of racket sports coaches.